2000
DOI: 10.1021/la990557w
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Growth of Chromophore-Functionalized (3-Aminopropyl)triethoxysilane Self-Assembled on Silicon

Abstract: We have used X-ray reflectivity, ellipsometry, and X-ray photoelectron spectroscopy to characterize self-assembled films of (3-aminopropyl)triethoxysilane (APS) functionalized with a photosensitive chromophore. Using the evolution of film thickness with time devoted to initial APS adsorption on the surface, we obtain a model for the structure and growth dynamics of the film. LA990557W(43) Dulcey, C.; Gru ¨neberg, K. Unpublished results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
104
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 42 publications
15
104
0
1
Order By: Relevance
“…[112,113] Nevertheless, aminosilanes, and particularly 3-aminopropyltrialkoxysilanes (APS), have been used extensively as adhesion promoters and the well-known reactivity of amines has been exploited for the introduction of various functionalized molecules. APS layers were used to covalently bind fullerenes, [114,115] chromophores, [116,117] and fluorophores, [118,119] and to coordinate to a zinc porphyrin. [120] In addition, photoresponsive spiropyran molecules were covalently attached to an APS layer and used to induce reversible changes in wettability upon switching to a more polar zwitterionic merocyanine isomer, triggered by the absorption of UV light.…”
Section: Self-assembly Of Functionalized Alkylsilanes and Chemical Trmentioning
confidence: 99%
“…[112,113] Nevertheless, aminosilanes, and particularly 3-aminopropyltrialkoxysilanes (APS), have been used extensively as adhesion promoters and the well-known reactivity of amines has been exploited for the introduction of various functionalized molecules. APS layers were used to covalently bind fullerenes, [114,115] chromophores, [116,117] and fluorophores, [118,119] and to coordinate to a zinc porphyrin. [120] In addition, photoresponsive spiropyran molecules were covalently attached to an APS layer and used to induce reversible changes in wettability upon switching to a more polar zwitterionic merocyanine isomer, triggered by the absorption of UV light.…”
Section: Self-assembly Of Functionalized Alkylsilanes and Chemical Trmentioning
confidence: 99%
“…[112,113] Dennoch wurden Aminosilane, insbesondere 3-Aminopropyltrialkoxysilane (APS), häufig als Haftvermittler verwendet. Die wohlbekannte Reaktivität der Amine machte man sich zur Einführung zahlreicher funktionalisierter Moleküle zunutze: APS-Schichten wurden kovalent an Fullerene, [114,115] Chromophore [116,117] und Fluorophore [118,119] gebunden sowie an ein Zinkporphyrin koordiniert. [120] Des Weiteren wurden photoaktive Spiropyranmoleküle kovalent an APS-Schichten angebracht.…”
Section: Selbstorganisation Funktionalisierter Alkylsilane Und Chemisunclassified
“…methyl ethyl ketone and toluene) from lube oil filtrates [102][103][104] [105]. Other examples of SRNF applications involve the enrichment of aromatic components in refinery streams [106], deacidification of crude oil [107] and desulfurization of gasoline [108]. More recently, a study by Othman et al demonstrated the applicability in biodiesel production [109].…”
Section: Applications Of Srnf Membranesmentioning
confidence: 99%
“…Besides the water content and the solvent nature, other experimental parameters as the temperature [31,94,105], reaction time [106] and silane concentration plays a crucial role in the surface coverage and in the thickness of the grafted layer and it's homogeneity.…”
Section: Silylation Reaction Mechanism and Influence Of The Reactionmentioning
confidence: 99%